The New Encyclopedia of Southern Culture : Volume 14: Folklife - Ferris, William R.; Hinson, Glenn (Book collections on Project MUSE., 2009)
Demonstrates how folklife remains a vital part of communities' self definitions. The entries demonstrate that southern folklife is dynamically alive and everywhere around us, giving meaning to the everyday unfolding of community life.